The EduPARK Mobile Augmented Reality Game: learning value and usability - Pombo, Lúcia (2018)
Augmented Reality (AR) technology and games can enhance motivation for learning. When combined with mobile devices, AR technology can promote authentic learning in outdoor environments, such as urban parks. These spaces can be used for Science Education, particularly, for environmental education and nature conservation. The EduPARK project combines these elements and follows a design-based research approach to develop an interactive mobile AR game to be explored by students, teachers and the general public, as visitors, in a specific urban park, integrating four interdisciplinary educational guides. The app development involved four cycles of user testing and evaluation for progressive refinement, according to the users’ feedback in each cycle. The focus of this paper is to analyze the users’ perceptions in the two last cycles of the app refinement, regarding its learning value and usability. The users were students of different school levels (24 of Basic Education; and 46 of Higher Education). Data collection involved a focus group interview, a questionnaire and the app’s usage data. Content analysis, descriptive statistics, and System Usability Scale (SUS) computing were conducted. Results revealed that the EduPARK app promotes learning, enjoyment and is easy to use. It achieved an excellent usability, according to younger students (85.8 of average SUS) and a good usability according to older students (70.9). From the last refinement cycle, the app’s final version has emerged, which is freely available to the public in the Google Store. In the future, more evaluation experiences are needed to better understand the benefits of this mobile AR game for learning in urban parks.